Hip resurfacing arthroplasty for patients with inflammatory arthritis: a systematic review. Issue 1 (January 2018) - Morse, Kyle W.; Su, Edwin P.
Introduction: Modern metal-on-metal hip resurfacing arthroplasty has led to decreased revision rates and high implant survival rates as compared to prior generations of resurfacing. Many of the series that report on resurfacing outcomes focus upon patients treated with a diagnosis of osteoarthritis. Patients with inflammatory arthritis such as rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are also treated in these series, however, their outcomes following resurfacing are underreported. The aim of this study was to determine complications that may occur following hip resurfacing in patients with inflammatory arthritis. A secondary aim was to determine functional outcomes following resurfacing. Methods: A search was performed in MEDLINE (PubMed/OVID), Cochrane Library, and Google Scholar. 5 studies met eligibility criteria. This review includes 196 hips; 120 had a diagnosis of AS or seronegative spondyloarthropathy and 76 had a diagnosis of RA or juvenile RA. 8 revisions were reported at a mean time of 64.2 (8.67-275.58) weeks. Results: Femoral neck fracture was the most common indication for revision, occurring in 3.06% of all hips at 34.5 weeks (16.0-52.0). 2 infections, 2 reports of acetabular radiolucency, and no dislocations were reported. The University of California at Los Angeles score, Harris Hip Score, and Range of Motion were the most common functional outcomes measured, which increased in the majority of studies following resurfacing. Conclusions: Femoral neck fracture was the most common reason for revision in patients with inflammatory arthritis following resurfacing and there were no dislocations reported. Following resurfacing, these patients have improved functional outcomes.